2018
DOI: 10.3390/ijerph15030553
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Expressed in Online Comments about Environmental Factors in the Tourism Sector: An Exploratory Study

Abstract: The object of this exploratory study is to identify the positive, neutral and negative environment factors that affect users who visit Spanish hotels in order to help the hotel managers decide how to improve the quality of the services provided. To carry out the research a Sentiment Analysis was initially performed, grouping the sample of tweets (n = 14459) according to the feelings shown and then a textual analysis was used to identify the key environment factors in these feelings using the qualitative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 63 publications
1
64
0
4
Order By: Relevance
“…SA aims to discover differentiated feedback using varied methodological approaches that focus on polarity, subject, and opinion holder [11]. In previous research, SA has been reported to be able to identify the sentiments about products [2,5,6]. Within SA techniques, text information can be tagged as pertaining to either of two categories: fact or opinion.…”
Section: Sentiment Analysis (Sa)mentioning
confidence: 99%
See 2 more Smart Citations
“…SA aims to discover differentiated feedback using varied methodological approaches that focus on polarity, subject, and opinion holder [11]. In previous research, SA has been reported to be able to identify the sentiments about products [2,5,6]. Within SA techniques, text information can be tagged as pertaining to either of two categories: fact or opinion.…”
Section: Sentiment Analysis (Sa)mentioning
confidence: 99%
“…In this respect it is important to properly implement the proposed process and correctly filter the user-generated content. Appropriate practices include the following: (i) removing the duplicate content; (ii) accessing only public UGC; (iii) collecting the data that can be grouped or classified around a tag or topic, such as companies indexed in a ranking, companies that have won a prize, #hashtags, and so forth [2,5,7,19]. In this way, the dataset will be classified around a defined grouping [14,18].…”
Section: Data Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…PU is defined as how much an individual believes that using a particular system will improve their performance [32]. It is a measure of the subjective likelihood that a potential user will increase their work performance in an organization when using the technology [35]. The PEOU variable measures how much an individual believes that using a particular system is effort-free.…”
Section: Technology Acceptance Model (Tam) Variablesmentioning
confidence: 99%
“…Those outside yet accessible depend upon a parameter value that controls the probability that such a connection can occur and certain platforms change that probability. From the societal analogs described as example from where the facility to access non-local associates can arise from, examples such as Twitter communities, Rotary Clubs and others are mentioned (examples of this in real world scenarios are discussed in [15,16]). These aggregations of users provide a meeting place for the choice process of new friendships to occur outside of the pre-existing locality and provide the means for the accessibility but are not explicitly modeled.…”
Section: Introductionmentioning
confidence: 99%